Chiral symmetry breaking and the Josephson current in a ballistic superconductor-quantum wire-superconductor junction - Krive, I.V.; Gorelik, L.Y.; Shekhter, R.I.; Jonson, M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2004)
We evaluate the Josephson current through a quasi-1D quantum wire coupled to bulk superconductors. It is shown that the interplay of Rashba spin–orbit interaction and Zeeman splitting results in the appearence of a Josephson current even in the absence of any phase difference between the superconductors. In a transparent junction (D ≃ 1) at low temperatures this anomalous supercurrent Jan appears abruptly for a Zeeman splitting of the order of the Andreev level spacing as the magnetic field is varied. In a low transparency (D << 1) junction one has Jan µ Ö D̅ under special (resonance) conditions. In the absence of Zeeman splitting the anomalous supercurrent disappears.We have investigated the influence of dispersion asymmetry induced by the Rashba interaction in quasi-1D quantum wires on the critical Josephson current and have shown that the breakdown of chiral symmetry enhances the supercurrent.